Mitochondrial MPTP: A Novel Target of Ethnomedicine for Stroke Treatment by Apoptosis Inhibition - Li, Yangxin; Sun, Jiayi; Wu, Ruixia; Bai, Jinrong; Hou, Ya; Zeng, Yong; Zhang, Yi; Wang, Xiaobo; Wang, Zhang; Meng, Xianli (Frontiers in Pharmacology, 2020)
Mammalian mitochondrial permeability transition pore (MPTP), across the inner and outer membranes of mitochondria, is a nonspecific channel for signal transduction or material transfer between mitochondrial matrix and cytoplasm such as maintenance of Ca2+ homeostasis, regulation of oxidative stress signals, and protein translocation evoked by some of stimuli. Continuous MPTP opening has been proved to stimulate neuronal apoptosis in ischemic stroke. Meanwhile, inhibition of MPTP overopening-induced apoptosis has shown excellent efficacy in the treatment of ischemic stroke. Among of which, the potential molecular mechanisms of drug therapy for stroke has also been gradually revealed by researchers. The characteristics of multi-components or multi-targets for ethnic drugs also provide the possibility to treat stroke from the perspective of mitochondrial MPTP. The advantages mentioned above make it necessary for us to explore and clarify the new perspective of ethnic medicine in treating stroke and to determine the specific molecular mechanisms through advanced technologies as much as possible. In this review, we attempt to uncover the relationship between abnormal MPTP opening and neuronal apoptosis in ischemic stroke. We further summarized currently authorized drugs, ethnic medicine prescriptions, herbs, and identified monomer compounds for inhibition of MPTP overopening-induced ischemic neuron apoptosis. Finally, we strive to provide a new perspective and enlightenment for ethnic medicine in the prevention and treatment of stroke by inhibition of MPTP overopening-induced neuronal apoptosis.